SIKAP MASYARAKAT DESA HUTAN TERHADAP PERUBAHAN DAN ALIH GUNA KAWASAN HUTAN MENJADI KAWASAN PERTAMBANGAN BATUBARA - Hafizianor Hafizianor (Universitas Lambung Mangkurat, 2016)
Change and use change forest into coal mining area has led to changes in the biophysical environment and social environment forest villagers. This study aimed to analyze the attitudes towards changes in environmental conditions biophysical and social environment of rural communities around the mining of coal before and after the change and use change forest into coal mining region. The study was conducted in Tanah Bumbu, South Kalimantan. The method used to achieve the purpose of the study is the quantitative approach. Quantitative data from the data collecting through questionnaire will be processed through the editing process is researching the answers to the questionnaire, coding which classifies respondents consisting of three scales and then calculate the frequency based data distribution and tabulation. The results of the study public attitudes to change and use change forest into the area of coal mining and public attitudes show a positive attitude, which means it is a change to changing environmental conditions biophysical and social environment of rural communities around the mining of coal before and after the change and transfer of forest land use be a coal mining region.